The Modus Operandi of Children as the Offender in Committing Human (A study in Kepolisian Resor Kota Besar Surabaya) - Chintya Dewi Saraswati (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
Children who are supposed to be protected by the state, law, and society can be an organised criminal offender such as human trafficking. In Surabaya, there were 32 human trafficking cases since 2011-2018 that was handled by Polrestabes (Capital City Police) Surabaya where the offenders were children. The problem in this research is the Modus Operandi of children as the offender in the act of human trafficking. This research used empirical research method with socio-legal and criminological approach. From the research result, the author found out that children that committed human trafficking were caused by the influence of economic factor, environment, and lifestyle. From those causes, the modus operandi of the children as the offender in committing human trafficking was by getting acquainted in social media like Facebook and Whatsapp and then make an offer to the potential buyer. The National Police has two ways in preventing and tackling children as the offenders of human trafficking which are by prevention and repressive effort Children